Coping With Memory Shortcomings Before Exams :The Case of Third Year LMD Students of English at Abdelhamid Ibn Badis University (Mostaganem) - BENNEKRELA, NABIL (My University, 2019)
College students confront an issue known as memory shortcomings which they experience in several minutes before tests.The study is an attempt to peruse many researches by well-known scholars about reasons behind the problem of forgetting information in tests period.The current study prevails the reasons behind memory shortcomings and how learners can deal with it in the EFL context with LMD English degree students of the University of Abdelhamid Ibn Badis_Mostaganem as a case study.We used two research tools,one was observation when we had to make a check list so as to attain the objectives,whereas the second one was the questionnaire that was administered to third year LMD English students to extract information which can assist in answering the research question.It has been found that a high rate of third year LMD learners in the department of English at Abdelhamid Ibn Badis_Mostaganem experince memory shortcomings minutes before they are given the exam sheets.And this is simply due to some factors which caused this phenomenon.
Keywords: Memory shortcomings,reasons,organizing and understanding,pictures.